STUDI TEKNO EKONOMI PERENCANAAN PEMBANGKIT LISTRIK MIKRO HIDRO (PLTMH) DI KECAMATAN KARERA KABUPATEN SUMBA TIMUR - Frans Likadja; Molina Olivia Odja; Stephanie I. Pella; Wenefrida T. Ina (Jurnal Media Elektro, 2022)
This study aims to measure the water potential of the Pahambur Wai River, in Nggongi Village, Karera District, East Sumba Regency to be used as a driving source for Micro Hydro Power Plants.This study aims to measure the water potential of the Pahambur Wai River, in Nggongi Village, Karera District, East Sumba Regency to be used as a driving source for Micro Hydro Power Plants. The research methods used are observation, area mapping, measurement of water flow and elevation, calculation of potential for electric power generated, Detail Engineering Design, cost calculation and economic feasibility.From the analysis and calculation, the maximum water flow of the Pahambur Wai River is 1,687 m3/s, minimum water flow is 0.054 m3/s. Probability availability is 70%, or 0.240 m3/s, with an effective elevation of 15 meters. The actual electric power generated is 20.44 kW. Type of turbine of MHPP is the Crossflow T14, D300 turbine, and coupled using a V belt, to a 3 phase synchronous generator, with a capacity of 25 kW.The plan for the construction and operation of the MHPP is economically feasible, as can be seen from the indicators of investment feasibility NPV, IRR, and Profitability Index.